The Impact of Prolotherapy and Steroid Injection on De Quervain's Tenosynovitis: A Retrospective Outcome Study - Tuğba Özüdoğru Çelik (Acta Medica Alanya)
Letter to the editor, Scientific Comment on of the article titled: "The Impact of Prolotherapy and Steroid Injection on De Quervain's Tenosynovitis: A Retrospective Outcome Study"